2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20184465
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of steroid modified tinea in tertiary care centre Lucknow

Abstract: <p class="abstract"><strong>Background:</strong> Rampant use and abuse of topical steroids has led to increase in number of cases of superficial dermatophytosis of skin, nail and hair. In most of the cases they are resistant to topical as well as oral antifungals even after prolong course of treatment. Our study aims to analyse epidemiological and microbiological profile of steroid modified tinea (SMT).</p><p class="abstract"><strong>Methods:</strong> Clinically diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This indicates disease exacerbation due to chronic steroid use despite initial masking of symptoms/reported relief. 15 Our study has shown that the use of DSS holds high statistical reliability. The statistical reliability was noted among both dermatology experts in dermatophytoses and dermatologists who are not experts in this area and residents/trainees.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This indicates disease exacerbation due to chronic steroid use despite initial masking of symptoms/reported relief. 15 Our study has shown that the use of DSS holds high statistical reliability. The statistical reliability was noted among both dermatology experts in dermatophytoses and dermatologists who are not experts in this area and residents/trainees.…”
Section: Discussionmentioning
confidence: 71%
“…Higher severity scores (of statistical significance) were noted among patients who used steroid creams and combination creams (antifungals with steroids and antibacterials). This indicates disease exacerbation due to chronic steroid use despite initial masking of symptoms/reported relief 15 …”
Section: Discussionmentioning
confidence: 99%